Guest

sinA-cosA+1÷sinA+cosA-1= 1÷ secA - tanA, by using identity sec×secA=1+tan×tanA.

sinA-cosA+1÷sinA+cosA-1= 1÷ secA - tanA, by using identity sec×secA=1+tan×tanA.

Grade:10

1 Answers

Arun
25758 Points
4 years ago

divide each term of the eqtn. by cosA 

tanA-1+secA/tanA+1-secA

multiply this eqtn wth tanA-(1-sec A)/ tanA-(1-secA) and apply sec2A= tan2A+1!!

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free